"El Sendajo del Quemao", una cueva artificial en la cuenca de Río Grande (Málaga) - Fernández-Ruiz, Juan; González Martín, Juan (Universidad de Málaga. Facultad de Filosofía y Letras, 2006)
Se da a conocer la primera y por ahora única cueva artificial de la cuenca de río Grande. Aunque sin materiales asociados, su morfología, con cámara circular y cámara secundaria, engrosa el repertorio del sur peninsular de este tipo de estructuras funerarias, íntimamente ligadas al megalitismo.

This article describes the first and only man-made cave in the Rio Grande ravine. Although no associated materials have been found, its morphology, which includes both a circular main chamber and a secondary chamber, allows its inclusion in the Southern Peninsular funerary structure repertoire. These structures are intimately linked to the Megalith Period.
Keywords: Cuevas - Río Grande (Málaga)